The Importance of Unprotected Areas as Habitat for The Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) on Java, Indonesia - Nanang Irawan; Satyawan Pudyatmoko; Pujo Semedi Hargo Yuwono; Muhammad Tafrichan; Anthony J. Giordano; Muhammad Ali Imron (Fakultas Kehutanan Universitas Gadjah Mada, 2020)
Protected areas play important roles for protecting many endangered species in Indonesia. However, very limited information regarding roles of protected areas and non-protected areas for supporting the habitat of less-concerned carnivores in Java, leopard cat (Prionailurus bengalensis javanensis). We aim to assess the relative roles of non-protected areas for the habitat of this cat on the highly fragmented and populated island of Java. We develop species distribution modelling, using Maxent by integrating various sources of presence data of this species and environmental data. Our finding confirms that leopard cat can life in various habitat types but mainly patchy forest areas. While most of the protected areas are suitable for the habitat of this smallest cat on Java, the non-protected areas provide much larger areas for its habitat (66.8 %). Our findings highlighted the importance of maintaining connectivity among habitat patches in non-protected areas, habitat protection using current government policy on high conservation value forest and essential ecosystems areas. Pentingnya Kawasan Non Lindung sebagai Habitat Kucing Hutan (Prionailurus bengalensis javanensis Desmarest, 1816) di Jawa, IndonesiaIntisariKawasan lindung memainkan peran penting dalam melindungi banyak spesies yang terancam punah di Indonesia. Walaupun demikian, informasi mengenai peran kawasan lindung dan kawasan non lindung untuk mendukung habitat karnivora yang kurang mendapat perhatian di Jawa, kucing hutan (Prionailurus bengalensis javanensis), sangat terbatas. Penelitian ini bertujuan untuk menilai peran kawasan non lindung sebagai habitat kucing hutan di Pulau Jawa, pulau yang sangat terfragmentasi dan padat penduduk. Kami mengembangkan pemodelan distribusi spesies, menggunakan Maxent dengan mengintegrasikan berbagai sumber data kehadiran spesies kucing hutan dan data lingkungan. Temuan kami menegaskan bahwa kucing hutan dapat hidup di berbagai jenis habitat tetapi habitat utamanya adalah kawasan hutan yang agak terbuka. Meskipun sebagian besar kawasan lindung sesuai untuk habitat kucing terkecil di Jawa ini, kawasan non lindung justru menyediakan area yang jauh lebih besar untuk habitat kucing hutan (66,8 %). Temuan kami juga menyoroti pentingnya menjaga konektivitas antar habitat di kawasan non lindung dan perlindungan habitat dengan menggunakan kebijakan pemerintah saat ini tentang hutan Bernilai Konservasi Tinggi dan Kawasan Ekosistem Esensial.